ICT cluster: The engine of knowledge-driven growth in Finland - Laura Paija (The Research Institute of the Finnish Economy (ETLA), 2000)
The momentous growth in the information and communications technology (ICT) industry has marked the rapid industrial restructuring in Finland. The welfare of the economy is increasingly connected to a sector that has incredible growth potential and that relies on knowledge-based factors of production. Today, the sector accounts for a third of exports while in 1980 the share was 4 per cent. Despite the prominent role of the Finnish ICT equipment industry both in domestic and international contexts, the cluster development lies heavily on the foundation built in the operator sector during the early phases of the history. In the retrospect, the ICT cluster looks like an outcome of an well-orchestrated master plan. However, many of the factors with great impact on national competitiveness have been more or less coincidental in past- or at least motivated by other than industrial policy objectives. – – Tieto- ja viestintäklusterin ennennäkemätön kasvuvauhti on johtanut Suomessa nopeaan teolliseen rakennemuutokseen. Talouden menestys kytkeytyy enenevässä määrin alaan, jolla on mittaamattomat kasvumahdollisuudet ja joka hyödyntää luotuja tuotannontekijöitä. Alan osuus viennistä on noussut kolmannekseen vuoden 1980 neljästä prosentista. Huolimatta viestintälaiteteollisuuden merkittävästä kotimaisesta ja kansainvälisestä asemasta klusterin kilpailukyvyn kehitys pohjautuu pitkälti puhelintoiminnan varhaisiin kehitysvaiheisiin. Tieto- ja viestintäklusterista on kehittynyt kansainvälisesti merkittävä innovaatiojärjestelmä, joka on kuin taitavasti toteutetun suunnitelman tulos. Kuitenkin monet merkittävästi kansalliseen kilpailukykyyn vaikuttaneet tekijät ovat menneisyydessä syntyneet muista kuin talouspoliittisista lähtökohdista.
Keywords: 330; Information and communication technology (ICT) cluster; competition; specialisation; innovation patterns; industrial policy; Tieto- ja viestintäklusteri; kilpailu; erikoistuminen; innovaatiorakenteet; teollisuuspolitiikka; Informationswirtschaft; Informationstechnik; Clusteranalyse; Finnland